Behavioural study on individual share investors in Singapore. - Chua, Soo Kiat. (2008)
This Applied Research Project (ARP) was carried to find out how demographic factors affect the trading behaviour of the individual share investors and to determine the relative importance of different factors in influencing the individual share investors’ investment decisions.